What Types of Courses Best Prepare Students? - Mueting, Megan; Marshall, Jeremy L. (My University, 2017)
I wanted to do a study on how people learn best because I think it’s important for instruction to be effective for productive learning. A lot of professors or future teachers need to know what style of class will work best for their learners. I wanted to know if college students learn best in lecture style, studio style or lab style classes and I thought college students would learn best in studio. In my results, I found that most students liked lecture style classes but learned best from lab style classes. I hope to take the knowledge I gained from this research into my classroom in the future.